Foaming configuration method for electrodes of hydrogen electrolysis cell
By using nickel foamed electrodes in hydrogen electrolytic cells, optimizing foam structure and catalyst deposition, the conductivity and wettability of the electrodes are enhanced, and the problems of insufficient conductivity and stability of traditional electrode materials are solved, achieving efficient gas diffusion and liquid Penetration balance reduces hydrogen production costs and improves energy conversion efficiency.
Patent Information
- Application Number
- CN202411454751.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-07
AI Technical Summary
The conductivity and chemical stability of traditional hydrogen electrolytic cell electrode materials are insufficient, resulting in inefficient charge transfer and imbalance between gas diffusion and liquid penetration, affecting the electrolytic efficiency and hydrogen production cost.
Using nickel foam as electrode material, through electrochemical polishing or pickling pretreatment, design foam structures with porosity and micron-level pore sizes, select precious metal or non-precious metal catalysts for uniform deposition, and use plasma treatment and Coating hydrophilic coatings enhance wetting and corrosion resistance, perform systematic assembly and performance testing, and cycle iterative optimization.
It improves the conductivity and chemical stability of the electrode, balances gas diffusion and liquid penetration, reduces the cost of hydrogen production, and improves the energy conversion efficiency and the long-term stability of the electrolytic cell.
Smart Images

Figure CN119265601A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a foaming configuration method for hydrogen electrolyzer electrodes. Background Art
[0002] The hydrogen electrolyzer is an important device for producing hydrogen, and the electrode, as the core component of the electrolyzer, has a direct impact on the electrolysis efficiency, energy consumption and hydrogen production cost due to its performance. Traditional electrode materials and structures may have some limitations, such as: Insufficient conductivity and chemical stability: Electrode materials need to have both good conductivity and chemical stability in the electrolysis environment to ensure efficient charge transfer and long-term use without degradation. The balance problem between gas diffusion and liquid penetration: During the electrolysis process, the generation and release of gases (mainly hydrogen and oxygen) require effective diffusion channels, and the electrolyte also needs to fully penetrate the electrode surface to promote the reaction. Traditional electrode structures may find it difficult to achieve the optimal balance between the two.
[0003] Therefore, based on the above technical problems, it is necessary to design a foaming configuration method for hydrogen electrolyzer electrodes. Summary of the invention
[0004] The purpose of the present invention is to provide a method for foaming the electrodes of a hydrogen electrolyzer, aiming to solve the problem that traditional electrode materials in the prior art may not be able to simultaneously meet good electrical conductivity and chemical stability for long-term use in an electrolysis environment, which affects the effective transfer of charges and the durability of the electrodes, and the poor balance between gas diffusion and liquid penetration.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for foaming a hydrogen electrolyzer electrode, characterized in that it comprises the following steps:
[0007] Step 1: Selection and pretreatment of electrode substrate:
[0008] Select suitable substrate: Based on cost-effectiveness and application requirements, nickel foam is selected as the basic material of the electrode because of its good conductivity and chemical stability;
[0009] Surface pretreatment: Use electrochemical polishing or pickling to clean the substrate surface to remove impurities and form an active surface that is conducive to catalyst attachment;
[0010] Step 2: Foam structure optimization:
[0011] Design foam parameters: Based on theoretical calculations and simulations, determine the optimal porosity (generally between 60% and 90%), pore size (micrometer level) and its distribution to balance the needs of gas diffusion and liquid penetration;
[0012] Structural forming: chemical foaming or physical foaming process is used to precisely control the formation of the foam structure and ensure a uniform pore structure;
[0013] Step 3: Catalyst deposition and modification:
[0014] Catalyst selection: Select appropriate catalyst materials based on cost and catalytic efficiency, such as precious metals (platinum, iridium) or non-precious metal catalysts (nickel-based alloys, cobalt-based materials);
[0015] Uniform coating: Use methods such as impregnation, electrodeposition or spray pyrolysis to evenly distribute the catalyst on the surface and internal pores of the foam electrode to ensure the effective use of each active site;
[0016] Step 4: Surface modification and stabilization:
[0017] Wettability enhancement: plasma treatment or hydrophilic coating can enhance the wettability of the electrode surface to facilitate rapid penetration of the electrolyte.
[0018] Corrosion-resistant treatment: applying a protective layer or coating with corrosion-resistant materials to improve the corrosion resistance of the electrode during long-term electrolysis;
[0019] Step 5: Assembly and performance test:
[0020] Electrode assembly: Precisely assemble the optimized foam electrode with other components (such as diaphragm and current collector) to form a complete electrolysis unit;
[0021] Performance verification: Under simulated or actual working conditions, the assembled electrolyzer is tested for performance, including indicators such as electrolysis efficiency, gas purity, long-term stability and energy consumption;
[0022] Step 6: Feedback and Optimization:
[0023] Data analysis: Based on the test results, evaluate the actual effect of the electrode foaming configuration and identify potential areas for improvement;
[0024] Iterative cycle: Based on feedback, adjust the electrode design, material selection or preparation process, and continuously optimize to achieve higher performance standards.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. In this scheme, the comprehensive performance of the electrode is improved by carefully selecting the substrate (such as nickel foam), optimizing the foam structure parameters, fine catalyst deposition, surface modification, strict assembly testing and feedback loop optimization. This method not only improves the conductivity and chemical stability of the electrode, but also optimizes the balance between gas diffusion and liquid penetration through foam structure design. At the same time, a cost-effective and catalytically efficient catalyst is used, and the wettability and corrosion resistance of the electrode are enhanced through surface treatment. Finally, through systematic testing and optimization, the high-performance operation of the electrolyzer is ensured, the cost of hydrogen production is reduced, and the energy conversion efficiency is improved.
[0027] 2. In this scheme, a balance between gas diffusion and liquid penetration requirements is achieved through the precise design of the foam structure (porosity 60%-90%, micron-level pore size and its distribution). This design ensures that the gas can be effectively released during the electrolysis process, and the electrolyte can fully contact the electrode surface, promoting the efficient electrochemical reaction. In the selection of catalysts, not only the high catalytic efficiency of precious metals such as platinum and iridium is considered, but also more cost-effective non-precious metal catalysts such as nickel-based alloys and cobalt-based materials are explored. The uniform coating technology of impregnation, electrodeposition or spray pyrolysis is ensured to ensure the uniform distribution of the catalyst on the electrode surface and in the pores, thereby maximizing the catalytic activity and reducing the cost of hydrogen production.
[0028] 3. In this scheme, the surface properties of the electrode are improved: the surface modification treatment includes plasma treatment and the coating of a hydrophilic coating. These measures significantly enhance the wettability of the electrode, allowing the electrolyte to penetrate into the interior of the electrode more quickly. At the same time, the corrosion-resistant treatment improves the durability of the electrode and ensures stability and efficiency during long-term electrolysis.
[0029] 4. Through rigorous assembly testing and performance verification, including evaluation of key indicators such as electrolysis efficiency, gas purity, long-term stability and energy consumption, the invention provides a closed-loop process from design, testing to optimization. Data analysis and feedback loop iteration mechanisms ensure continuous technical improvement, and can adjust any performance bottlenecks found to continuously improve the overall performance of the electrolyzer. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0031] Figure 1 A flow chart of the method for configuring the foaming of hydrogen electrolyzer electrodes according to the present invention; DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] See also Figure 1 , the present invention provides the following technical solutions:
[0035] A method for foaming a hydrogen electrolyzer electrode, characterized in that it comprises the following steps:
[0036] Step 1: Selection and pretreatment of electrode substrate:
[0037] Select suitable substrate: Based on cost-effectiveness and application requirements, nickel foam is selected as the basic material of the electrode because of its good conductivity and chemical stability;
[0038] Surface pretreatment: Use electrochemical polishing or pickling to clean the substrate surface to remove impurities and form an active surface that is conducive to catalyst attachment;
[0039] Step 2: Foam structure optimization:
[0040] Design foam parameters: Based on theoretical calculations and simulations, determine the optimal porosity (generally between 60% and 90%), pore size (micrometer level) and its distribution to balance the needs of gas diffusion and liquid penetration;
[0041] Structural forming: chemical foaming or physical foaming process is used to precisely control the formation of the foam structure and ensure a uniform pore structure;
[0042] Step 3: Catalyst deposition and modification:
[0043] Catalyst selection: Select appropriate catalyst materials based on cost and catalytic efficiency, such as precious metals (platinum, iridium) or non-precious metal catalysts (nickel-based alloys, cobalt-based materials);
[0044] Uniform coating: Use methods such as impregnation, electrodeposition or spray pyrolysis to evenly distribute the catalyst on the surface and internal pores of the foam electrode to ensure the effective use of each active site;
[0045] Step 4: Surface modification and stabilization:
[0046] Wettability enhancement: plasma treatment or hydrophilic coating can enhance the wettability of the electrode surface to facilitate rapid penetration of the electrolyte.
[0047] Corrosion-resistant treatment: applying a protective layer or coating with corrosion-resistant materials to improve the corrosion resistance of the electrode during long-term electrolysis;
[0048] Step 5: Assembly and performance test:
[0049] Electrode assembly: Precisely assemble the optimized foam electrode with other components (such as diaphragm and current collector) to form a complete electrolysis unit;
[0050] Performance verification: Under simulated or actual working conditions, the assembled electrolyzer is tested for performance, including indicators such as electrolysis efficiency, gas purity, long-term stability and energy consumption;
[0051] Step 6: Feedback and Optimization:
[0052] Data analysis: Based on the test results, evaluate the actual effect of the electrode foaming configuration and identify potential areas for improvement;
[0053] Iterative cycle: Based on feedback, adjust the electrode design, material selection or preparation process, and continuously optimize to achieve higher performance standards.
[0054] In a specific embodiment of the present invention, a suitable substrate is selected: nickel foam is preferred because of its unique physical and chemical properties. It not only has a high conductivity, ensuring the rapid transfer of charge, but also has good chemical stability. It is not easy to undergo chemical reactions in an electrolytic environment, resulting in performance degradation. In addition, the porous structure of nickel foam provides convenient conditions for gas diffusion and electrolyte penetration. Surface pretreatment: electrochemical polishing removes tiny surface unevenness and impurities through electrolytic reaction to form a smooth and pollution-free surface, which helps to enhance the adhesion of subsequent catalysts. Pickling uses a strong acid solution to dissolve oxides and other impurities on the surface, exposing a clean, highly active metal surface, providing a good adhesion platform for the catalyst. Step 2: Foam structure optimization and design of foam parameters: Theoretical calculation and simulation are important tools in modern materials science. They help researchers accurately predict the effects of different porosities and pore sizes on gas diffusion and liquid penetration. The ideal porosity range (60%-90%) can ensure sufficient gas channels without excessively hindering the flow of electrolyte. The optimization of pore size ensures that bubbles can rise smoothly and reduce resistance. Structural forming: Chemical foaming generates gas through chemical reactions to form a foam structure inside the material, while physical foaming is achieved through physical means (such as high-temperature steam or gas injection). These methods require precise control technology to ensure the consistency and repeatability of the foam structure, which is especially important for large-scale production. Step 3: Catalyst precipitation Accumulation and modification of catalyst selection: Precious metal catalysts such as platinum and iridium are favored for their excellent catalytic activity, but the high cost has prompted researchers to explore non-precious metal alternatives, such as nickel-based alloys and cobalt-based materials. These materials can also show good catalytic performance after optimization, reducing overall costs and uniform coating: The choice of coating technology depends on the physical and chemical properties of the catalyst and the uniformity requirements of the required coating. The impregnation method is simple and easy, and is suitable for filling large pore structures; electrodeposition forms a catalytic layer on the electrode surface through electrochemical reactions, and the control is precise; spray pyrolysis can quickly form a uniform film at high temperature, which is suitable for coating of complex surfaces. Regardless of the method, the goal is to ensure the uniform distribution of the catalyst on the electrode surface and in the internal pores, maximizing the catalyst Efficiency, step 4: surface modification and stabilization treatment: Wettability enhancement: Improved wettability is crucial to electrolysis efficiency; plasma treatment is an advanced surface treatment technology that bombards the electrode surface to not only remove surface pollutants, but also change the surface chemical properties, introduce oxygen-containing functional groups, and increase hydrophilicity; in addition, coating a layer of hydrophilic coating (such as polymer or siloxane-based materials) can also significantly increase the penetration rate of the electrolyte, ensuring the continuity and efficiency of the electrochemical reaction; corrosion resistance treatment: During the electrolysis process, the electrode material is exposed to the electrolyte for a long time and is prone to corrosion; by applying a corrosion-resistant protective layer on the electrode surface, such as oxide, nitride or ceramic coating, the corrosive medium can be effectively isolated and the service life of the electrode can be extended;Selecting corrosion-resistant substrates or considering the corrosion resistance of materials in the design stage is also an important strategy; Step 5: Assembly and performance testing: Electrode assembly: The precise assembly of electrodes is a prerequisite for ensuring the efficient operation of the entire electrolysis unit; this requires good matching and sealing between the foam electrode and other components (such as proton exchange membranes or alkaline electrolyte membranes as diaphragms, and effective current collection systems) to prevent leakage and short circuits, while ensuring that the electrolyte is evenly distributed to facilitate the reaction; Performance verification: Performance testing is a key step in verifying the success of electrode design; By simulating laboratory environments or directly testing under industrial application conditions, the performance of the electrolyzer can be comprehensively evaluated, including but not limited to electrolysis efficiency (i.e., the ratio of electrical energy converted to hydrogen energy), gas purity (ensuring high-quality output of hydrogen and oxygen), and long-term stability (electrodes under continuous operation). performance retention capability) and energy consumption (reflecting the economy of the system); these test results provide a direct basis for subsequent optimization; Step 6: Feedback and optimization: Data analysis: Based on the in-depth analysis of performance test data, researchers can identify weak links in electrode design, material selection or preparation process; through statistical methods and data modeling, quantify the impact of various factors on performance, and provide scientific guidance for subsequent improvements; Cycle iteration: Optimization is a continuous process. Based on feedback information, the research team needs to continuously adjust the design plan, such as changing electrode structure parameters, trying new catalysts, optimizing surface treatment technology, etc., and then perform performance tests again, forming a "design-test-optimization" cycle iteration process; This process promotes the maturity of technology and the continuous improvement of performance, and is the core link in promoting the advancement of hydrogen energy technology. ;
[0055] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for foaming electrodes in a hydrogen electrolyzer, characterized in that: It includes the following steps: Step 1: Selection and pretreatment of electrode substrate: Select suitable substrate: Based on cost-effectiveness and application requirements, nickel foam is selected as the basic material of the electrode because of its good conductivity and chemical stability; Surface pretreatment: Use electrochemical polishing or pickling to clean the substrate surface to remove impurities and form an active surface that is conducive to catalyst attachment; Step 2: Foam structure optimization: Design foam parameters: Based on theoretical calculations and simulations, determine the optimal porosity (generally between 60% and 90%), pore size (micrometer level) and its distribution to balance the needs of gas diffusion and liquid penetration; Structural forming: chemical foaming or physical foaming process is used to precisely control the formation of the foam structure and ensure a uniform pore structure; Step 3: Catalyst deposition and modification: Catalyst selection: Select appropriate catalyst materials based on cost and catalytic efficiency, such as precious metals (platinum, iridium) or non-precious metal catalysts (nickel-based alloys, cobalt-based materials); Uniform coating: Use methods such as impregnation, electrodeposition or spray pyrolysis to evenly distribute the catalyst on the surface and internal pores of the foam electrode to ensure the effective use of each active site; Step 4: Surface modification and stabilization: Wettability enhancement: plasma treatment or hydrophilic coating can enhance the wettability of the electrode surface to facilitate rapid penetration of the electrolyte. Corrosion-resistant treatment: applying a protective layer or coating with corrosion-resistant materials to improve the corrosion resistance of the electrode during long-term electrolysis; Step 5: Assembly and performance test: Electrode assembly: Precisely assemble the optimized foam electrode with other components (such as diaphragm and current collector) to form a complete electrolysis unit; Performance verification: Under simulated or actual working conditions, the assembled electrolyzer is tested for performance, including indicators such as electrolysis efficiency, gas purity, long-term stability and energy consumption; Step 6: Feedback and Optimization: Data analysis: Based on the test results, evaluate the actual effect of the electrode foaming configuration and identify potential areas for improvement; Iterative cycle: Based on feedback, adjust the electrode design, material selection or preparation process, and continuously optimize to achieve higher performance standards.
Citation Information
Cited By
Rare earth metal electrolytic furnace discharging robot and tail end compliance control method and system thereof
CN120620202A